Volunteer [compact disc] (Columbia Nashville, 2018)
After releasing a Bob Dylan tribute album in 2017, Old Crow Medicine Show returns with a brand new studio album, which was recorded at the historic RCA Studio A in Nashville. Their latest includes the single Flicker & Shine.